2020
DOI: 10.1007/s12672-020-00384-4
|View full text |Cite
|
Sign up to set email alerts
|

TSH Level and Risk of Malignancy in Patients with Bethesda Category IV Thyroid Nodules

Abstract: Fine needle aspiration biopsy does not permit to distinguish between benign and malignant follicular thyroid lesions (category IV in the Bethesda Cytopathology System). Some reports have suggested an association between increased serum TSH levels and thyroid cancer, so the aim of this study was to investigate the association between TSH levels and malignancy in patients with follicular thyroid nodules. Therefore, we conducted a retrospective study of all subjects who underwent surgical treatment for Bethesda I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
(35 reference statements)
0
4
1
Order By: Relevance
“…One study suggested that a thyrotropin cutoff point of ≥ 2.1 mU/I and an age cutoff point of ≥ 47 years were significantly associated with a diagnosis of malignancy. 7 Although the current study did not study malignancy, the results showed that the mean age at nodule diagnosis was higher in patients who had abnormal vs normal most recent thyrotropin levels: 69 vs 62 years, respectively. Future studies could determine whether a certain initial thyrotropin value or age could be used as a cutoff for requiring further thyrotropin monitoring to check for development of hyperthyroidism or hypothyroidism.…”
Section: Discussioncontrasting
confidence: 55%
“…One study suggested that a thyrotropin cutoff point of ≥ 2.1 mU/I and an age cutoff point of ≥ 47 years were significantly associated with a diagnosis of malignancy. 7 Although the current study did not study malignancy, the results showed that the mean age at nodule diagnosis was higher in patients who had abnormal vs normal most recent thyrotropin levels: 69 vs 62 years, respectively. Future studies could determine whether a certain initial thyrotropin value or age could be used as a cutoff for requiring further thyrotropin monitoring to check for development of hyperthyroidism or hypothyroidism.…”
Section: Discussioncontrasting
confidence: 55%
“…Measurement of serum TSH is the initial laboratory test for all patients with thyroid nodules. Normal or elevated levels of TSH express a nonfunctioning nodule, and in large studies are associated with a higher risk of thyroid cancer [16,17]. Low or suppressed levels are associated with hyperthyroidism and a radioisotope scan with iodine-123 or technetium-99m pertechnetate must be performed.…”
Section: Paraclinical Assessment and Managementmentioning
confidence: 99%
“…It triggers the secretion of IGF-1, and insulin regulates the expression of thyroid genes to control the proliferation and differentiation of thyroid cells. Furthermore, expression of TSH receptors in extrathyroidal tissues (specifically in adipose tissue) means that TSH can promote the differentiation of pre-adipocytes to mature adipocytes, and in the presence of insulin, TSH exerts mitogenic properties [ 12 ]. In this review, we summarize the latest evidence regarding the molecular links between obesity and thyroid cancer development and discuss emerging diagnostic and therapeutic implications.…”
Section: Introductionmentioning
confidence: 99%